Barriers of Delivering Nursing Care to Children at Intensive Care Units: A Mixed Method Study - Dhamin, Sura Saleem; Bakey, Serwan Jafar (Iraqi National Journal of Nursing Specialties, 2024)
Objective(s): To determine barriers for delivering nursing care for children at Intensive Care Units. Methods: A mixed method research, employing (convergent parallel design) was used in this study. A non-probability (purposive) sampling of 60 nurses were employed, 15 of them were included in the qualitative part of the study. The data were collected from three different intensive care units from January 3rd to February 20th, 2024, using the performance obstacles assessment questionnaire for the quantitative part of the study. An official permission to use the study questionnaire was obtained from the corresponding author. A semi-structured interview technique was used to collect the data. It took about 45-60 minutes for each participant to complete interview and record their responses. Quantitative data analysis has been established by using SPSS version 23, and the qualitative data analysis have been established based on thematic analysis. Results: Quantitative results presented barriers including all domains (environmental barriers, organization barriers, technological barriers, task barriers, and family barriers) in which the mean of all domains was 2.61 and higher. In addition, qualitative results showed that nurses who work at children intensive care unit were faced by several barriers during care delivery for children such as environmental barrier, technological barrier, task barrier, organizational barrier, and family barrier. Conclusions: Pediatric nurses were confronting barriers during delivering care to children due to lack of family awareness about care, lack of appropriate resources and devices, nursing shortage, and absence of clear protocol. Recommendations: Efforts should be prioritized toward finding solutions for all the barriers faced by pediatric nurses to ensure better quality of healthcare services.